Fire dynamics distinguish grasslands, shrublands and woodlands as alternative attractors in the Central Great Plains of North America. (November 2014) - Ratajczak, Zak; Nippert, Jesse B.; Briggs, John M.; Blair, John M.; Sala, Osvaldo
Summary This review synthesizes evidence that altered fire frequency drives discontinuous ecosystem transitions from mesic grasslands to shrublands or woodlands in the Central Great Plains, USA. Long‐term fire manipulations reveal that grassland to shrubland transitions are triggered when fire‐free intervals increase from 1–3 years to ≥ 3–8 years, and longer fire returns (˜10 years or more) result in transitions to woodlands. Grazing and soil properties alter these fire thresholds. Grassland to shrubland transitions are abrupt and exhibit nonlinear relationships between driver and state variables. Transitions to shrublands and woodlands exhibit hysteresis, where reintroducing frequent fires does not reverse transitions in management‐relevant time‐scales (decades). Nonlinear transitions and hysteresis emerge because grasses generate positive feedbacks with fire that create strong demographic barriers for shrub and tree establishment. Fire‐free intervals allow shrubs and trees to reach a size sufficient to survive fire, reproduce and disrupt the fire feedback loop through competition. Synthesis. Mesic grasslands, shrublands and woodlands constitute self‐reinforcing states (alternative attractors) separated by critical fire frequency thresholds. Even without major shifts in climate, altered fire frequency can produce dramatic state changes, highlighting the importance of fire for predicting future ecosystem states. Local management should focus on prevention of unwanted transitions rather than post hoc restoration.